Low Golimumab Trough Levels at Week 6 Are Associated With Poor Clinical, Endoscopic and Histological Outcomes in Ulcerative Colitis Patients: Pharmacokinetic and Pharmacodynamic Sub-analysis of the Evolution Study. (16th April 2019) - Magro, F; Lopes, S; Silva, M; Coelho, R; Portela, F; Branquinho, D; Correia, L; Fernandes, S; Cravo, M; Caldeira, P; Sousa, H T; Patita, M; et al.
Abstract: Background and Aims: Golimumab has an established exposure-response relationship in patients with ulcerative colitis [UC]. However, the association of serum golimumab trough levels [TL] with objective markers of disease activity, such as endoscopic and histological activity scores and concentrations of biomarkers, remains less understood. This report describes the relationship of serum golimumab TL at the end of the induction period [Week 6] with clinical, endoscopic, histological, and biomarker parameters. Methods: This was an open-label, uncontrolled, prospective and interventional study. Moderate to severely active UC patients naïve to biologic therapy were treated with golimumab. Serum golimumab TL and faecal calprotectin levels were measured at baseline [Week 0 of induction] and Week 6. Results: A total of 34 patients completed the induction phase [Week 6] and were included in this analysis. Overall, 47.1% and 14.7% of patients achieved clinical response and remission with significantly higher serum golimumab TL in patients with early response or remission [3.7 μg/mL vs 1.3 μg/mL, p = 0.0013; and 3.1 μg/mL vs 1.7 μg/mL, p = 0.0164, respectively]. In addition, golimumab TL were significantly higher in patients achieving histological remission [4.2 μg/mL vs 1.7 μg/mL, p = 0.0049]. Week 6 golimumab TL were inversely correlated with the total Mayo score [rs = -0.546; p = 0.0008], the Mayo endoscopic subscore [rs = -0.381; p = 0.0262], the Geboes histological activity score [rs = -0.464; p = 0.0057], and faecal calprotectin levels [rs = -0.497; p = 0.0044]. Conclusions: A higher early exposure to golimumab is associated with a better objective response in active UC patients and appears to drive the outcome at Week 6.